“Efecto de cinco dosis de humus de lombriz en el cultivo de tomate (lycopersicon esculentum mill), en suelos ácidos, sector aucaloma- San Martín – Perú” - Saavedra Alva, Harry (2010)
The present research was realized with the aims to study comparatively the behavior of the tomato, variety Big River, with application located of different doses of earthworm in acid soils, seeking to improve the performance and profitabílity, in the farm Aucaloma of San's Martín National University- Tarapoto, located in the sector Aucaloma to 15 Km from Tarapoto, continuing the road to Cumbaza's San Antonio comprehension of San Roque's district province of Lamas and region San Martín. The design of blocks complete was utilizad at random DBCA, with 6 treatments and 4 repetitions, of the realized evaluations the following results were obtained: the humus of earthworm of 1 O and 6t/ha, it did effect in the cultivate with regard to the height (48.6 cm and 48.15 cm), in number of flowers for plants (18.85 and 14.73).Whereas the treatments with 6t/ha of humus; 1 O t/ha and 8t/ha of humus, obtained higher average of clusters of floral/plant (5.68,5.45 and 5.18).With the dose of 1 O t/ha of humus and 8t/ha of humus majar number of fruits was obtained by plant (9.23 and 8.78). lt 10t/ha of humus, with 599.75 g fruits/crops there obtained the majar performance (18550 kg/ha) wíth the majar performance (18550 kg/ha) with economic profitability of 33/100 cents of new sol for every new invested sol. Key words: tomato, Big River, humus carthworm, acid grounds, aplication located, dose, plant height, flowers far each plant, flowers clusters for each plant, fruits weight at harvest, productíon.